Cytosolic acidification as a signal mediating hyperosmotic stress responses in Dictyostelium discoideum - Pintsch, Tanja (BioMed Central, 2001)
BACKGROUND: Dictyostelium cells exhibit an unusual response to hyperosmolarity that is distinct from the response in other organisms investigated: instead of accumulating compatible osmolytes as it has been described for a wide range of organisms, Dictyostelium cells rearrange their cytoskeleton and thereby build up a rigid network which is believed to constitute the major osmoprotective mechanism in this organism. To gain more insight into the osmoregulation of this amoeba, we investigated physiological processes affected under hyperosmotic conditions in Dictyostelium. RESULTS: We determined pH changes in response to hyperosmotic stress using FACS or (31)P-NMR. Hyperosmolarity was found to acidify the cytosol from pH 7.5 to 6.8 within 5 minutes, whereas the pH of the endo-lysosomal compartment remained constant. Fluid-phase endocytosis was identified as a possible target of cytosolic acidification, as the inhibition of endocytosis observed under hypertonic conditions can be fully attributed to cytosolic acidification. In addition, a deceleration of vesicle mobility and a decrease in the NTP pool was observed. CONCLUSION: Together, these results indicate that hyperosmotic stress triggers pleiotropic effects, which are partially mediated by a pH signal and which all contribute to the downregulation of cellular activity. The comparison of our results with the effect of hyperosmolarity and intracellular acidification on receptor-mediated endocytosis in mammalian cells reveals striking similarities, suggesting the hypothesis of the same mechanism of inhibition by low internal pH.